138k views
4 votes
Solve the equation
1/3(9k+3)=-2(k-8)

Solve the equation 1/3(9k+3)=-2(k-8)-example-1
User Xaria
by
5.6k points

2 Answers

6 votes

Answer:

k=3

Explanation:

User Megalomono
by
5.4k points
6 votes

Answer:

k = 3

Explanation:

step 1: simplify both sides of the equation

(
(1)/(3)) (9k) + (
(1)/(3)) (3) = (-2) (k) + (-2) (-8) (distribute)

3k + 1 = -2k +16

step 2: add 2k to both sides

3k + 1 + 2k =-2k + 16 + 2k

5k + 1 = 16

step 3: subtract 1 from both sides

5k + 1 - 1 = 16 - 1

5k = 15

step 4: divide both sides by 5


(5k)/(5) =
(15)/(5)

k = 3

User Jtouzy
by
5.2k points